2021
DOI: 10.34172/jrhs.2021.38
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrients Intake and Stomach Cancer Risk in Iran: A Hospital-based Case-Control Study

Abstract: Background: Stomach cancer (SC) is one of the most common cancers in the world. Dietary risk factors of SC are not fully understood. This study aimed to investigate the association between macronutrient intakes and the risk of SC. Study design: A hospital-based case-control study. Methods: The data were obtained from a hospital-based case-control study conducted at the Cancer Institute of Iran from 2010 to 2012. Patients were 40 years or older and were diagnosed with SC in less than one year with no history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(40 reference statements)
1
7
0
Order By: Relevance
“…Higher fat consumption in the case group in the present study could also be related to increased intake of saturated fats that constituted 27% of total fats. Saturated fats are known to be strong predictors of GC [17,[20][21][22]36,45] as observed in our study and were found to stimulate tumorigenesis at the molecular level [48].…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Higher fat consumption in the case group in the present study could also be related to increased intake of saturated fats that constituted 27% of total fats. Saturated fats are known to be strong predictors of GC [17,[20][21][22]36,45] as observed in our study and were found to stimulate tumorigenesis at the molecular level [48].…”
Section: Discussionsupporting
confidence: 59%
“…Elevated intakes of polyunsaturated fats, specifically omega-6 fatty acids, increased GC risk in the present study. Previous findings on the effects of polyunsaturated fats on GC risk are contradictory, whereby positive [48], negative [25,45], and no associations [36] were observed. Discrepancies could be related to the source of omega-6 fatty acids and whether it is heat-treated.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations